AKTIVITAS SOSIAL EKONOMI MASYARAKAT NELAYAN DI DESA RANDOMAYANG KECAMATAN BAMBALAMOTU KABUPATEN PASANGKAYU - Suardin Abd. Rasyid; Andi Mascunra Amir (KINESIK, 2022)
This study aims to, First; explain the pattern of socio-economic activities of the fishing community, Second; explain the factors that influence socio-economic activities in fishing communities in Ramdomayang Village, Bambalamotu District, Pasangkayu Regency. The data in this study were obtained through observation and interviews with a number of informants who were taken purposively. The results of the study show that the socio-economic activities of the fishing community in Randomayang Village include fishing, farming, all of which are still carried out in traditional ways.This causes the socio-economic welfare of fishermen to not experience significant changes to date. In addition, this village also seems that the tradition of cooperation is still quite strongly embedded in the lives of fishermen as part of the socio-cultural system that they adhere to and practice. All of these things, both fishing and farming activities as well as mutual cooperation activities for various purposes and interests color the economic social activities and social interactions of fishermen. The socio-economic activities of the fishing community in this village are predominantly influenced by the physical environment resources, as well as the socio-cultural system of the local community.